Silica-Supported Co3O4 Nanoparticles as a Recyclable Catalyst for Rapid Degradation of Azodye - Ali Baghban; Esmail Doustkhah; Sadegh Rostamnia; Khadijeh Ojaghi Aghbash (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2016)
In this paper, silica nanoparticles with particle size of 10-20 nm were selected as a support for the synthesis of Co3O4 nanoparticles by impregnation of silica nanoparticles in solution of Co(II) in a specific concentrations and then calcination to 800 oC. This nanocomposite was then, used as a catalyst for oxidative degradation of methyl orange (MO) with ammonium persulfate in aqueous media. Effect of pH, temperature, contact time, amount of oxidant and catalyst were studied in the presence of manuscript. Scanning electron microscope (SEM), electron dispersive spectroscopy (EDS), FT-IR, and ICP-AES analyses were used for analysis of silica-supported Co3O4 (Co3O4/SiO2). Treating MO with ammonium persulfate in the presence of Co3O4/SiO2 led to complete degradation of MO under the optimized conditions. Also, the catalyst exhibited recyclability at least over 10 consecutive runs.